COVID-19 and metabolic disease: mechanisms and clinical management. Issue 11 (November 2021) - Steenblock, Charlotte; Schwarz, Peter E H; Ludwig, Barbara; Linkermann, Andreas; Zimmet, Paul; Kulebyakin, Konstantin; Tkachuk, Vsevolod A; Markov, Alexander G; Lehnert, Hendrik; de Angelis, Martin Hrabě; Rietzsch, Hannes; Rodionov, Roman N; et al.
Summary: Up to 50% of the people who have died from COVID-19 had metabolic and vascular disorders. Notably, there are many direct links between COVID-19 and the metabolic and endocrine systems. Thus, not only are patients with metabolic dysfunction (eg, obesity, hypertension, non-alcoholic fatty liver disease, and diabetes) at an increased risk of developing severe COVID-19 but also infection with SARS-CoV-2 might lead to new-onset diabetes or aggravation of pre-existing metabolic disorders. In this Review, we provide an update on the mechanisms of how metabolic and endocrine disorders might predispose patients to develop severe COVID-19. Additionally, we update the practical recommendations and management of patients with COVID-19 and post-pandemic. Furthermore, we summarise new treatment options for patients with both COVID-19 and diabetes, and highlight current challenges in clinical management.